Anatomic Implants in Breast Reconstruction: A Comparison of Outcomes and Aesthetic Results Compared to Smooth Round Silicone Implants. (15th March 2019) - Agochukwu-Nwubah, Nneamaka; Boustany, Ashley; Wetzel, Margaret; Maus, Jacob; Rinker, Brian
Abstract: Background: Direct comparison studies of outcomes and aesthetic satisfaction of anatomic implants compared to other implants are scarce in the literature. Objectives: The objective of this study was to compare outcomes and aesthetic satisfaction of patients who underwent breast reconstruction with anatomic implants vs other implants (smooth round silicone). Methods: A retrospective chart review was performed of patients who underwent implant-based breast reconstruction over 3 years. Outcomes including complications, number of surgeries, need for revisions, and aesthetic satisfaction of patients were tracked and compared. Results: A total of 156 patients met inclusion criteria for this study. A total of 123 underwent reconstruction with a round implant, and 33 underwent reconstruction with an anatomic implant. Of the 156 patients, 38 underwent a 1-stage direct-to-implant reconstruction and the remainder underwent a 2-stage implant reconstruction. The round and anatomic implant groups did not differ with regards to number of surgeries, revisions, utilization of contralateral symmetry procedures, implant-related reoperations, complications, implant loss, infection, capsular contracture, and seroma. The Breast Q survey had a response rate of 27%. On all parameters, the round and anatomic implant groups did not significantly differ. Conclusions: There were no significant differences among round and shaped implants in regards to complications, revision surgeries, and overall outcomes. Furthermore, patients showed no differences regarding satisfaction and well-being when surveyed on the Breast Q survey. The decision of implant choice in breast reconstruction should be based on surgeon comfort and the patient's needs/body type. : Level of Evidence: 4